Hubungan Antara Inisiasi Menyusui Dini Dengan Kecepatan Waktu Pengeluaran Plasenta Pada Kala III Persalinan Di Ruang Dahlia I RSU USD Gambiran Kota Kediri - Yunarsih Yunarsih; Dwi Rahayu (coba, 2016)
Breaseeding (Early initiation) or the beginning of early breastfeeding is a natural process of restoring a human baby to suckle, by allowing the baby to find and suck the milk itself, within the first hour of the beginning of life. touch the baby's hands at the nipple and surrounding, sucking and licking a baby on the nipple stimulates the hormone oxytocin can help the uterus contract, helping expulsion of the placenta and reduce maternal bleeding. Normally, the placenta will be separated in less than 30 minutes after birth. The purpose of this study is the Knowing the relationship between early initiation of breastfeeding plasenta.Rancang spending time with the speed of this study was a cohort (longitudinal prospective). In this study, the speed of early initiation of breastfeeding in question are researchers doing early initiation of breastfeeding in a way after the baby is born and then dried body and the baby's head and placed the baby the mother's chest between the two breasts and then the mother and baby covered together. While time expulsion of the placenta (the third stage) is the time between the issuance of the fetus and placenta using random sampling and diambilsampelsebanyak tehniksampling 15 orangsesuaikriteriayang determined. To analyze the relationship between the relationship between early initiation of breastfeeding with spending time digunakanujistatistik T testdengan help SPSS20ForWindows.Berdasarkandari ujihasilanalisakorelasi T test using SPSS20 For Window obtained hasilp (0,037) < (0.05),a which means that H0 and H1 accepted meaning adahubunganyangsignifikanantarahubungan between breaseeding with placenta spending time at Dahlia Lounge I RSU USD Gambiran Kediri. This is because of the stimulation of the nipples when IMD stimulates oxytocin expenditures that increase the force of contraction uetus. In further research should consider other factors that increase the strength of uterine contractions. KeyWord: early breastfeeding initiation, speed removal of placenta